2006
DOI: 10.1002/j.0022-0337.2006.70.3.tb04079.x
|View full text |Cite
|
Sign up to set email alerts
|

Scope of Practice Comparison: A Tool for Curriculum Decision Making

Abstract: The proportion of claims filed for specific dental procedures (ADA codes # 05110, 05120, 03320, 03330, 04260, 02150) between January 1, 2000 and June 30, 2004 by Texas general practitioners participating in a preferred provider network was compared to the proportion of these procedures performed by students graduating from the three Texas dental schools during the same period. Analysis of the data revealed that Texas dental students provide class two amalgam restorations in permanent teeth (02150) at approxima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2008
2008
2009
2009

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Accurate measures of the type and frequencies of services delivered in the practice setting are useful for quality improvement assessment, practice improvement goals, comparison with professional educational objectives, and benchmarking for practitioners performing self‐assessment. Data for these purposes are generally obtained from dental claims data, chart reviews, national surveys of dentists’ self‐reported activities, or patient report of services received (1–3). There is little empirical evidence, however, supporting the reliability or validity of these sources for measuring what has actually transpired in the provider–patient interaction.…”
mentioning
confidence: 99%
“…Accurate measures of the type and frequencies of services delivered in the practice setting are useful for quality improvement assessment, practice improvement goals, comparison with professional educational objectives, and benchmarking for practitioners performing self‐assessment. Data for these purposes are generally obtained from dental claims data, chart reviews, national surveys of dentists’ self‐reported activities, or patient report of services received (1–3). There is little empirical evidence, however, supporting the reliability or validity of these sources for measuring what has actually transpired in the provider–patient interaction.…”
mentioning
confidence: 99%